2007
DOI: 10.1007/s11998-007-9024-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating service lifetimes in weathering: an optimistic view

Abstract: Directly correlating lifetime to coating composition by using standardized, artificial exposures, or even natural exposure, is often very difficult. However, significant progress can be made by breaking down the problem into smaller questions, which can be separately addressed. If one understands the physical parameters that affect end-use properties, then one can also group, and thus correlate, properties according to whether they depend on processes at the surface or in the bulk of a coating, or whether they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Croll [23,24] carried out one of the first systematic studies on the drying behavior of solvent-cast polymer films. He showed that the magnitude of the residual drying stress in a polymer coating is a function of the Young's modulus (E) of the polymer, the volume fraction of solvent at the point of solidification (φ s ), and the volume fraction of solvent in the dry film (φ r ), according to:…”
Section: Polymer Filmsmentioning
confidence: 99%
“…Croll [23,24] carried out one of the first systematic studies on the drying behavior of solvent-cast polymer films. He showed that the magnitude of the residual drying stress in a polymer coating is a function of the Young's modulus (E) of the polymer, the volume fraction of solvent at the point of solidification (φ s ), and the volume fraction of solvent in the dry film (φ r ), according to:…”
Section: Polymer Filmsmentioning
confidence: 99%
“…With many of these systems, simultaneous control over cure kinetics and solvent release allows for enhanced adhesion and impermeability as does polymer structure (the presence of polar groups) and the mechanism of cure, that is, polymerization after (but not before) application. Some systems (vinyl esters, unsaturated polyesters), as well as those binders crosslinking via condensation-type polymerization mechanisms (phenolics and other formaldehyde-based systems), exhibit high internal stress from shrinkage on polymerization (especially when applied at excessive film thicknesses) and this may be disadvantageous to sustained adhesion [23,24]. Epoxies, however, curing by addition polymerization, shrink less and exhibit much improved adhesion, making very valuable binders for barrier coatings.…”
Section: C12 Thermosetting Bindersmentioning
confidence: 99%
“…Perhaps, more importantly, certainly with thermosetting (chemically curing systems) internal stress development on drying, arising from solvent release and/or from polymerization, will increase as film thickness increases [24,34]. The stress produced by the conversion of thick films (even strongly adherent epoxies) is capable of overcoming the adhesion of the coating, even over abrasive blasted surfaces.…”
Section: C6 Film Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…8 To analyze and improve the correlations between laboratory and field data and increase the understanding of coating behavior during accelerated exposure conditions it is of relevance to quantify the underlying physical and chemical mechanisms and develop overall modeling tools. [9][10][11] Mathematical models can also help to map the coupling of individual rate phenomena.…”
Section: Introductionmentioning
confidence: 99%